Perlindungan Hukum Data Pribadi Pengguna Layanan Transportasi Digital Dalam Perspektif Perbandingan Hukum - I Made Dwi Aya Praditya; Bagus Gede Ari Rama; Anak Agung Ayu Ngurah Sri Rahayu Gorda; I Gede Agus Kurniawan (Jurnal Yustitia, 2025)
The development of digital transportation services such as Gojek is highly dependent on personal data, but various cases of data leaks highlight the weakness of legal protection in Indonesia. This has prompted the need for comparison with Japan, which has stronger regulations through the APPI. This study aims to identify and examine the regulation of personal data of users of digital transportation services in Indonesia and compare it with the law in Japan. This study applies a normative legal research method using a legislative approach and legal concept analysis. The findings show that data protection in Indonesia is regulated in the 1945 Constitution and the PDP Law, which require data controllers such as Gojek to ensure lawful, secure, and accountable data management. However, its implementation still faces institutional challenges. In comparison, Japan, through its independent supervisory agency PPC, shows progress in supervision and a high culture of compliance. While Indonesia's PDP Law is normatively comprehensive, its effectiveness still awaits the establishment of a supervisory agency and complete implementing regulations.